(3HZjI GdBed aj JQJjH GdcGeds - (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, GdeHQO , CHh GdYHGS,J (B286 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdfYe GdSGHZI hGdMce GdHGdZIhHYO aEf GdCOH gi CTQa UfGYI HcJSHgG GdZGad hCQHM HVGYI jbJfjgG GdYGbd s
(3BNQgG (B:s
(3bGd GdCUeYi (B: (3cGf ef OYGA CHj GdeLjH (B: (3Gdgde GLYd NjQ Yedi eG bGQH CLdi bGd hcGf jbhd ai OYGFg Gddge dG JcdfG Edi CfaSfG afYLR hdG Edi GdfGS afVjY s
(3GdcJGH eQJH Ydi afhf hebSe Ydi CQHYjf HGHkG HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1382s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
Keywords: (3GdCOHs